La citación por boletas fuera del domicilio del demandado y la nulidad procesal en materia civil. - Garcés Estrada, Javier Geovanny (2022)
The present research work is about “A LEGAL ANALYSIS OF THE FRAMEWORK THAT EXISTS IN OUR SYSTEM REGARDING THE FORMS OF SUMMONS HAS BEEN CONSIDERED MADE AN ADEQUATE APPLICATION OF THE PRINCIPLES OF SPEED AND DUE PROCESS IN ORDER TO GUARANTEE FOR SOUND ADMINISTRATION OF JUSTICE WITHIN THE LAW”. The research has focused on the study specifically, if required by subpoena in the workplace of the defendants in order to achieve a consistent analysis, this is why the legal regulations do not allow the subpoena to be made, none of this conflicts with the principle of speed in accordance with what has been determined in the General Organic Code of Processes. In addition, an analysis of nullity procedure has been established, all the aspect have been thoroughly studied the most significant general aspects within civil proceedings have been studied, in addition to the conceptualization and characteristics, to project the investigation towards nullity due if they ignore the subpoena of according to what is dictated by the General Organic Code of Processes but also verify the serious consequences can occur if you fail to comply with it. Finally, it has been of great importance to identify the case studies, in which nullity of procedure can be verified by the administrators of justice ruled by the regulations that have been determined, especially in civil matters, as well as verifying the legal consequences that this declaration of nullity during the judicial proceedings, and the affectation towards the procedural parties.